Effect of patient education and healthcare campaigns on medication adherence in co-morbid patients - Abdullah, Marwah Yakoop; Alanazi, Afrah Farhan; Alandijani, Abdulaziz Amin; Alshehri, Mazen Saleh; Aljuaid, Faris Saud; Saab, Noura Abdullah Bin; Alshihri, Reem Ali; Ali, Majed Hassan; Alghamdi, Mohammed Abdullah; Hammad, Marwa Yusuf; Althumali, Jameel Sami (International Journal Of Community Medicine And Public Health, 2023)
Co-morbidities are characterized by the presence of multiple chronic diseases within a single individual. They pose an escalating healthcare challenge and managing this growing burden, particularly with non-communicable diseases, has become a major concern. However, a significant impediment to effective management lies in medication nonadherence. The importance of medication adherence has long been a focus of healthcare literature, yet many comorbid patients tend to underestimate its significance, leading to health deterioration. Research studies indicate alarmingly low adherence rates in comorbid patients. To address this issue, patient education and healthcare campaigns have become essential tools in enhancing adherence. The research, which commenced on October 19, 2023, was initiated after an exhaustive review of existing academic literature. Multiple databases, such as PubMed, Web of Science, and Cochrane, were employed for this comprehensive literature review, utilizing a wide array of medical terminology combinations. The study aims to shed light on potential strategies and educational approaches to enhance medication adherence in comorbid patients. Findings from this research have the potential to influence healthcare policy, the design of tailored interventions, and overall healthcare delivery improvements for co-morbid patients, ultimately leading to enhanced health outcomes, reduced costs, and an improved quality of life.